Experience from Turkish centers participating in the Early Access Program (EAP): Preliminary real-world safety data of nivolumab (nivo) combined with ipilimumab (ipi) in pre-treated advanced melanoma patients - Nuri Karadurmus; Mehmet Ali Nahit Sendur; Burcak Karaca; Omer Fatih Olmez; Ilhan Hacibekiroglu; Hasan Senol Coskun; Serkan Degirmencioglu; Yasemin Kemal; Saadettin Kilickap; Ahmet Taner Sumbul; Burc Aydin; Hande Turna; et al. (Journal of Oncological Sciences, 2018)
Objective: We aimed to evaluate the safety of nivolumab + ipilimumab (nivo + ipi) in advanced melanoma patients who had relapsed after ≥1 line of systemic treatment in a real-world setting. Methods: Adult patients with advanced melanoma who had progressed after ≥1 line of systemic treatment were eligible for nivo 1 mg/kg + ipi 3 mg/kg Q3W × 4, followed by nivo 3 mg/kg Q2W until progression, or unacceptable toxicity for up to 24 months in the Early Access Program (EAP) in Turkey. Treatment-related adverse events (TRAEs) were recorded and analyzed. Results: Forty patients who received at least one dose of nivo + ipi were included. Median number of doses (Nivo + ipi and nivo alone) were 4 with a median follow-up of 19 weeks. Thirty patients (75%) were alive and 24 patients (60%) were on treatment. TRAEs of any grade and grade 3–4 occurred in 53% and 20% of the patients, respectively. One patient died due to TRAEs (colitis and diarrhea) after the second dose of nivo + ipi. Median times to onset and resolution of TRAEs were 6 and 3 weeks, respectively. Eleven patients (28%) discontinued treatment for reasons other than TRAEs. TRAEs of any grade led to discontinuation in 5 patients (13%). Most of the TRAEs were reversible when managed with available guidelines. Discussion: Safety profile of N + I was found to be consistent with early reports. Increased experience with the management of TRAEs of immunotherapies, short follow-up and ≥2 line real-world setting may account for lower TRAEs rates. Long-term follow is needed. Keywords: Nivolumab, Ipilimumab, Immunotherapy, Melanoma